On Solution of Fractional Model of Human Liver under Hybrid Fractional Derivative - Ahmad, Shabir; Ullah, Aman; ul, Ali Akg; Baleanu, Dumitru (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we generalize the mathematical model of the human liver by recently introduced hybrid fractional derivative. We achieve the existence and uniqueness results via Schauder's and Banach fixed point theorems, respectively. We use the Laplace transformation technique to attain the series type solution of the human liver model. In the end, we give the conclusion of the manuscript and future research direction.